Sarcopenia in the elderly, its causes and intervention through resistance exercises: integrative review (Research, Society and Development, 2022)
Objective: To relate the practice of resistance exercise and sarcopenia in the elderly. Methodology: This work is an integrative literature review, characterized by providing a way to synthesize knowledge and incorporate the practical applicability of important research findings. The searches were carried out mainly in the Scielo, PubMed, Virtual Health Library (VHL) and Google Scholar databases. Results and discussion: 162 articles were found in the consulted databases, after applying the inclusion and exclusion criteria, 7 studies were selected for analysis. The findings pointed to significant improvements for the prevention and treatment of sarcopenia through resistance training, as they demonstrated several positive effects related to lean mass, muscle mass, functional performance, strength and muscle quality, essential parameters to intervene with more excellence in the geriatric syndrome that is the problem at hand. Conclusion: Therefore, resistance training is proving to be the most effective means of exercise for the prevention and treatment of the disease. The elderly diagnosed with it showed several improvements due to anatomical and physiological adaptations. Therefore, from the perspective of increasingly assertive results, a broad view is suggested in future works that seek to develop new interventions through research.